DAMPAK LOOSE PARTS PADA KREATIVITAS ANAK DI RA NURUL ILMI - Pebriyanti, Diyan (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2023)
This study aims to determine the effect of using loose parts on increasing the creativity of children aged 5-6 years in RA Nurul Ilmi Pulau Birandang, Kec. camp. This type of research is a quantitative true experimental model. The population of this study were all children aged 5-6 years in class B1 and B2 at RA Nurul Ilmi Pulau Birandang, Kec. The camp has 24 children. So that the sample in this study consisted of 2 classes with a total of 24 children. Based on the results of research and data analysis, it can be concluded: The use of loose parts media has an effect on increasing the creativity of children aged 5-6 years at RA Nurul Ilmi Pulau Birandang, Kec. Kampa, this is proven by the results of t arithmetic > t table, (5.878>1.796) and a significance of <0.05 (0.000 <0.05), then Ho is rejected, Ha is accepted and the dominance of development is in the BSH category (Developing as expected). Suggestions in this study to increase creativity can be done with varied loose parts media so that each child is able to issue creative ideas and ideas in carrying out activities at school.